Workfare: Möglichkeiten und Grenzen - Susanne Koch; Gesine Stephan; Ulrich Walwei (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
One of the most far-reaching proposals for reform in the field of labour market policy is to link the receipt of transfer payments in general to a 'service in return' from the recipient. This concept operates under the name of workfare. This paper examines the possibilities and limits of workfare in dealing with labour market problems. This includes the labour supply effects, the life satisfaction of welfare recipients and the balancing of the labour market taking into account the fiscal consequences. The paper shows that one fundamental premise for the effectiveness of a wide-ranging workfare does not apply without restriction. Empirical findings suggest that employment increases life satisfaction even when the income level is controlled for. Thus workfare need not have a 'deterrent effect'. Furthermore the labour-market-policy utility as an activation alternative is limited due to the possible risks of displacement. Nevertheless, elements of workfare definitely have a place in the context of a wide-ranging set of labour market policy instruments.
Keywords: J64; J68; 330; Workfare; Transferleistung; aktivierende Arbeitsmarktpolitik; Workfare; Wirtschaftspolitische Wirkungsanalyse; Sozialhilfeempfänger; Deutschland